Análise de esgarçamento de costura em tecidos 100% algodão destinados a confecção de uniformes profissionais utilizando diferentes tipos de linha de costura e densidade de pontos - Baronio, Vanessa (2017)
Professional uniforms are used to identify, standardize, organize and provide wellbeing to employees of a company. To ensure that the uniforms meet the expectations of the user and have quality, standards are used that determine the raw material and sewing parameters to be used. The aim of this research was to expand the parameters of ABNT NBR 9925:2009 with the use of other types of sewing lines and other stitch density to analyze the behavior of seam splicing in the samples when submitted to dynamometer tests, and to compare the data obtained with samples tested in normal parameters established in the standard. With the result, it can be concluded that by decreasing the density of stitches and using seam threads, the resistance to crimping can be improved, thus interfering in the quality of the finished article.